Various pamphlets and circulars relating to Irish American politics - Celtic Club (Booklyn, New York); United States. Congress. Senate (1905)
Includes the pamphlets 'The Clansman, June 1905: souvenir of Celtic and Emmet clubs Irish picnic and games Celtic Park, N.Y.' (17 June 1906); 'Notes in reference to statements in the record of evidence before American Commission of Inquiry into conditions in Ireland' (31 Aug. 1929); Statements of John M. Costello and Richard F. Dalton, Charles T. Rice and Thomas H. Buckley before the Committees on Foreign Affairs and Foreign Relations of the U.S. House of Representatives and Senate (Feb. 1949); 'A refutation of the false attacks on Tom Barry, Malachy Conlon and Jeremiah Lennon (c.1950); 'American Friends of Ireland’s Ulster (c. 1950) and 'England’s Work' circular letter.
Keywords: Irish Americans -- Political activity -- 20th century; Ireland -- History -- 1922-